Energy Shift of the Atomic Emission Lines of He-like Ions Subject to Outside Dense Plasma - Chang, Tu-Nan; Fang, Te-Kuei; Sun, Rui; Wu, Chensheng; Gao, Xiang (Atoms, 2024)
We present an extension of our study of the energy shift of the atomic emissions subject to charged-neutral outside dense plasma following the good agreement between the experimental measurements and our recent theoretical estimates for the α and β emission lines of a number of H-like and He-like ions. In particular, we are able to further demonstrate that the plasma-induced transition energy shift could indeed be interpolated by the simple quasi-hydrogenic picture based on the application of the Debye–Hückel (DH) approximation for the n=3 to n=2 transitions of the He-like ions. Our theoretically estimated redshifts of those emissions may offer the impetus for additional experimental measurement to facilitate the diagnostic efforts in the determination of the temperature and density of the dense plasma.